PENTINGNYA INTERAKSI SOSIAL SERTA KESEIMBANGAN ANTARA HAK DAN KEWAJIBAN TERHADAP KINERJA AWAK KAPAL DI DERMAGA INTERNASIONAL TERMINAL PETIKEMAS SURABAYA - Nyoman Ardiana Listriyawati; Supangat - (UNIMAR AMNI Semarang, 2022)
Social interaction and the balance between the rights and obligations of the crew on board would determine whether or not the performance of the crew, especially on foreign-flagged ships. This happens due to several factors in social interaction and the social gap between their rights and obligations. The purpose of this study was to determine how positive and significant the effect of social interaction and the balance between rights and obligations on the performance of the crew. The method used by distributing questioners to respondents, namely ships crew with quantitative analysis by using multiple linier regression analysis, T test, F test and determination test to know the importance of social interaction and the balance between rights and obligations on crew performance. The result obtained in this study is that there is positive impact between social interaction and the balance between the rights and the obligations on the performance of ships crew. In the end, it is hoped that this research will be a reference to government (Disnaker) as policy maker and shipping companies as well as ship crew and other related parties.